2015
DOI: 10.1016/j.gtc.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Barrett’s Esophagus and Esophageal Adenocarcinoma

Abstract: Barrett’s esophagus (BE) is a common condition, and is the precursor to esophageal adenocarcinoma, a disease with increasing burden in the western world, especially in Caucasian males. The incidence of BE increased dramatically during the late-20th century and incidence estimates continue to increase, with a prominent male:female ratio. The prevalence is between 0.5 – 2.0 percent. A number of anthropomorphic and behavioral risk factors exist for BE including obesity and tobacco smoking, but GERD is the stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
161
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(170 citation statements)
references
References 162 publications
4
161
0
5
Order By: Relevance
“…In the last years, different studies have reported a decrease in most of the prevalent types of cancer, yet other types such as pancreatic, liver, thyroid, kidney and esophageal adenocarcinoma have increased, with up to a six-fold increase in the latter (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, different studies have reported a decrease in most of the prevalent types of cancer, yet other types such as pancreatic, liver, thyroid, kidney and esophageal adenocarcinoma have increased, with up to a six-fold increase in the latter (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In Western areas, the prevalence of BE is estimated to be between 0.5 and 6.8%, to arrive at 15% in symptomatic patients. 1 In Italy it has been estimated to be around 1.5%. 2,3 Chronic gastroesophageal reflux disease (GERD), a spectrum of hiatal hernia, gastroesophageal reflux, heartburn and regurgitation is a risk factor for both BE and erosive esophagitis (E).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that GERD is not always present in all patients with endoscopic diagnosis of BE or E and they may also share other modifiable risk factors such as smoking and overweight. 1,4,5 So far, epidemiologic data regarding coffee and tea consumption and risk of BE and E in Western areas are scarce and inconclusive. Only a few papers examined the relationship between coffee or tea intake and BE or E, while more data exist on the association with some types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of BE in patients undergoing endoscopy for any indication has been estimated to be at 1-2%, and this increases to 5-15% in patients that have GERD symptoms (3). Risk factors for BE include older age, male sex, Caucasian race, GERD symptoms (especially starting at a young age), central abdominal obesity, and possibly tobacco smoking (4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have estimated that patients with BE have a significantly increased risk (30-to 125-fold) of developing EAC compared to patients without BE (4). However, the absolute risk of EAC in patients with nondysplastic BE is low, at 0.1-0.5% per year, with most recent studies suggesting the incidence is on the lower end of that range (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%